An In-vitro study for comparing sealing quality of Bulk fill and Nano-hybrid composite resin in class II restorations - جحجاح محمد; منذر حداد (Latakia University Journal -Medical Sciences Series, 2023)
Aim of the study: To evaluate and compare marginal microleakage for bulk-fill and Nano-Hybrid composite in class II restorations. Materials and methods: 40 class II cavities were prepared in extracted human sound premolars. Premolars were extracted for orthodontic reasons. cavities dimensions were standardized as follow :4 mm length occlusocervically, 3 mm width buccolingually and 2 mm depth axially. The premolars were divided into two groups. Group 1: incrementally filled with Tetric N Ceram. Group 2 was filled with Tetric-N-Ceram bulk-fill composite in one layer. The samples were thermocycled for 200 cycles between 5-55°C. and then samples immersed in 0.5% methylene blue dye. All samples were mesiodistally sectioned and degree of microleakage scored under a light microscope. Results: study results show lower mean marginal microleakage in Tetric N Ceram group comparing with Tetric N Ceram Bulk-Fill group, with no statistically significant differences between the two groups. Conclusion: incremental placement technique and bulk-fill technique showed acceptable and similar results in terms of marginal microleakage. But non of the restorative techniques (incremental and bulk-fill techniques) completely eliminate marginal microleakage around the prepared restorations.